LA REPRESENTACIÓN DE IDENTIDADES QUEER ADOLESCENTES EN ‘SEX EDUCATION’ (NETFLIX, 2019-)1 - Lucía Gloria VÁZQUEZ RODRÍGUEZ,Francisco-José GARCÍA-RAMOS,Francisco A. ZURIAN HERNÁNDEZ (Fonseca, Journal of Communication, 2023)
This article provides an analysis of the representation of LGBTIQ+ teen identities in the first two seasons of ‘Sex Education’ (Netflix, 2019-). Utilising a methodology of analysis anchored in Queer Theory and in the concept of intersectionality, we will study the construction of those characters whose gender expression and/or sexual orientation defy the limits established by cisheteronormativity, as well as those whose desires (whether straight or not) do not fit within what Western societies understand as «normal», since we consider the rejection of the norm as a constitutive element of queerness